2015
DOI: 10.1149/2.0021510eel
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reactivity of KSi and NaSi Zintl Phases with Lithium

Abstract: The electrochemical reactions of NaSi and KSi Zintl phases with lithium (0-2.5 V) proceed very differently. Na/K is partially removed on first oxidation with a complete amorphization for NaSi or growth of a new crystallized K x Si phase for KSi. Upon discharge, metallic K is partially extruded and a Li-K-Si (Li 15 Si 4 -type) phase is formed. For NaSi, metallic Na is also chased on discharge but crystallization of Li-Na-Si (Li 15 Si 4 -type) phase is delayed at the second discharge. The amorphization of Li 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Apart from this, a comparison test of siloxene with bulk Si (Figure 8f) reveals some differences. Indeed, for Si, the CV presents two reduction peaks at 0.25 and 0.15 V and two oxidation ones at 0.32 and 0.50 V, 24,25 ascribed to the amorphization of bulk Si with lithiation and the final crystallization of Li 15 Si 4 in discharge followed by its delithiation into a-Si. Figure 8h shows bulk Si and siloxene in the sixth cycle, and it can be observed that the shoulder peak at 0.50 V in siloxene coincides with the oxidation peak of bulk Si, indicating the presence of an alloying reaction from the bulk Si impurities with Li.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Apart from this, a comparison test of siloxene with bulk Si (Figure 8f) reveals some differences. Indeed, for Si, the CV presents two reduction peaks at 0.25 and 0.15 V and two oxidation ones at 0.32 and 0.50 V, 24,25 ascribed to the amorphization of bulk Si with lithiation and the final crystallization of Li 15 Si 4 in discharge followed by its delithiation into a-Si. Figure 8h shows bulk Si and siloxene in the sixth cycle, and it can be observed that the shoulder peak at 0.50 V in siloxene coincides with the oxidation peak of bulk Si, indicating the presence of an alloying reaction from the bulk Si impurities with Li.…”
Section: ■ Results and Discussionmentioning
confidence: 99%